(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
G.B. Sultanova. Creativity of Furkat and his followers. The article examines the issues of creativity of Zakirjan Furkat and his followers, the tradition of creating works influenced by the work of the great poet Furkat. In particular, the works of Furkat and his followers, who after Fourcade created more than dozens of poetic works in the genre of muvashshah-gazelle, have been analyzed and scientifically proven.